2017
DOI: 10.1039/c7ce01407d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and optoelectronic properties of rigid 3D tetraindeno-fused spirofluorene with thioxanthene or dioxothioxanthene substitutes

Abstract: This work reports the synthesis and characterization of two blue emitters. Their 3D rigid structures are the appealing feature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…S5, ESI †). 36,39 Moreover, in the case of Spiro-F, two emission bands at 386 and 406 nm in CH 2 Cl 2 were observed, similar to those in the above-mentioned model compounds, which further indicates that the spiro-carbon linkages disrupt intramolecular electronic coupling. Furthermore, the symmetric mirror images of the absorption and emission spectra, as well as the very small Stokes shift (4 nm), coincide with the super-rigid molecular structure of Spiro-F.…”
Section: Optical and Electrochemical Propertiessupporting
confidence: 61%
See 4 more Smart Citations
“…S5, ESI †). 36,39 Moreover, in the case of Spiro-F, two emission bands at 386 and 406 nm in CH 2 Cl 2 were observed, similar to those in the above-mentioned model compounds, which further indicates that the spiro-carbon linkages disrupt intramolecular electronic coupling. Furthermore, the symmetric mirror images of the absorption and emission spectra, as well as the very small Stokes shift (4 nm), coincide with the super-rigid molecular structure of Spiro-F.…”
Section: Optical and Electrochemical Propertiessupporting
confidence: 61%
“…34 Interestingly, reports have shown that the S1/T1 values of Spiro-4S and Spiro-4SO 2 are the same. 36 Thus, we can conclude that the optoelectronic properties of Spiro-F mainly arise from its DFF backbone.…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 79%
See 3 more Smart Citations